Double-layer floor to mitigate in-structure shock of underground structures : a conceptual design - Zhou, Hongyuan (2012)
In-structure shock poses a great threat to equipment and devices in underground protective structures, preventing them from accomplishing designed tasks. Unlike traditional mitigation methods such as backfilling soft soil or sand around the buried structures and adding shock-isolation cushions to the equipment, a new structural design of underground structures are proposed by constructing an isolation slab, to which the equipment is attached. The excitation mechanism for the equipment attached to the slab is altered from the combination of flexural deflection and rigid body motion of the traditional floor to the response of the isolation slab. Analysis indicates that vertical shock level experienced by the equipment is effectively reduced. The in-structure shock mitigation approach proposed in the present study provides a supplement to the existing shock mitigation methods for underground structures.